An introduction to bioreactor hydrodynamics and gas-liquid mass transfer - Kadic, Enes, 1973-; Heindel, Theodore J., 1969- (Hoboken, New Jersey : Wiley, 2014)
"This book reviews and compares the major types of bioreactors used to produce renewable fuels, chemicals, medicines, and proteins, by providing an overview of the hydrodynamics and gas-liquid mass transfer operations in this equipment. These operations are important because they influence the quality and quantity of the desired material produced in the reactor. The text also discusses advantages and disadvantages of each bioreactor and provides a procedure for optimal bioreactor selection based on current process needs, giving chemical and mechanical engineers a practical, working reference"--
"This book provides an overview of hydrodyanmics and gas-liqiud mass transfer operations for various bioreactor configurations. It provides a summary of the available information for various bioreactors, reviews the relevant theories and experimental procedures, and provide a procedure for bioreactor selection"--
Modes of Operation -- Gas-Liquid Mass Transfer Models -- Experimental Measurement Techniques -- Modeling Bioreactors -- Stirred-Tank Bioreactors -- Bubble Column Bioreactors -- Airlift Bioreactors -- Fixed Bed Bioreactors -- Novel Bioreactors -- Figures of Merit -- Concluding Remarks -- Nomenclature.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Bioreactors; Bioreactors -- Fluid dynamics; SCIENCE -- Mechanics -- Dynamics -- Fluid Dynamics; Bioreactors; Bioreactors -- Fluid dynamics; Electronic books; Electronic books